PENGARUH SAFETY LEADERSHIP DAN SAFETY CLIMATE MELALUI SAFETY BEHAVIOR TERHADAP KECELAKAAN KERJA PADA KESEHATAN KARYAWAN - Anisfu Rahman; Eko Daryanto; Nur Aini (Jurnal Kesehatan dan Kedokteran, 2023)
Work accidents in the construction sector are still a work safety problem both in the world and in Indonesia that require attention from various parties. Safety behavior will make employees avoid the risk of accidents and create a sense of security at work so as to increase employee productivity. Several studies conducted by researchers found that safety behavior is influenced by leadership and company climate. The safety leadership approach can be one of the solutions to promote occupational safety and health more comprehensively. This study aims to determine the effect of safety leadership and safety climate through safety behavior on work accidents at PT Enseval Putera Megatrading Batam employees. The research design used in this research is descriptive and verification method using path analysis. With a sample of 52 respondents at PT Enseval Putera Megatrading Batam. The results showed that there was a significant influence between safety behavior on the work accident variable with a path value of 0.889, there was a significant influence between safety leadership on the Safety behavior variable with a path value of 0.550, there was a significant influence between safety leadership on the work accident variable with a path value paths of 0.530. Indirectly, safety leadership through safety behavior has no effect on work accidents because the test results are smaller than the direct value. There is a significant influence between safety climate on the safety behavior variable with a path value of 0.447. The path value is 0.478. Indirectly, safety climate through safety behavior has no effect on work accidents because the test results are smaller than the direct value.It is recommended to carry out more intense programs in the field of K3 by conducting trainings and scientific development